The Role of Innovative Marketing in Improving Market Share (A field study at Sepharma Pharmaceutical Industries) - بلدية , إياد (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aimed to clarify the role of innovative marketing in its dimensions (developing marketing technology, raising the value of resources, calculated risk, and sustainable innovation) in improving the market share of Seapharma Pharmaceutical Company in Syria. The descriptive and analytical approach was based on the opinion poll and the study of the phenomenon as it exists in reality, and the primary data was collected using the survey method and the questionnaire was adopted that was distributed to the employees of Seapharma Pharmaceutical Company, where a set of questions related to innovative marketing were formulated as a type of marketing and its role in improving the market share, in a way that serves the research. Secondary data was collected through what could be available from previous studies, research and indicators related to the topic of the research, and the data was analyzed using appropriate statistical analysis methods to process the data and extract results using SPSS. The study reached a number of results, including: The results of the main hypothesis demonstrated the existence of a statistically significant relationship between innovative marketing and improving the market share, as the correlation coefficient reached 0.717, and this indicates a good correlation between the two variables, The results of the first sub-hypothesis demonstrated the existence of a statistically significant relationship between the development of marketing technology and the improvement of the market share, as the correlation coefficient reached 0.682, and this indicates an acceptable correlation between the two variables, The results of the second sub-hypothesis also demonstrated the existence of a statistically significant relationship between raising the value of resources and improving the market share, as the correlation coefficient reached 0.620, and this indicates an acceptable correlation between the two variables.